2002
DOI: 10.1074/jbc.m105409200
|View full text |Cite
|
Sign up to set email alerts
|

Furin Proteolytically Processes the Heparin-binding Region of Extracellular Superoxide Dismutase

Abstract: Extracellular superoxide dismutase (EC-SOD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…This has been confirmed by another cross-sectional study [18]. The underlying mechanism of these associations may be explained by reduced proteolytic processing of mutated SOD3 protein [37] and a higher SOD3 level in blood plasma due to lower affinity to heparan sulphate in the extracellular matrix [20,38]. The present authors additionally found that the protective effect of this SNP on longitudinal FEV1 change appears in neversmokers.…”
Section: Sod Genetics In Copd and Bhr M Siedlinski Et Alsupporting
confidence: 74%
“…This has been confirmed by another cross-sectional study [18]. The underlying mechanism of these associations may be explained by reduced proteolytic processing of mutated SOD3 protein [37] and a higher SOD3 level in blood plasma due to lower affinity to heparan sulphate in the extracellular matrix [20,38]. The present authors additionally found that the protective effect of this SNP on longitudinal FEV1 change appears in neversmokers.…”
Section: Sod Genetics In Copd and Bhr M Siedlinski Et Alsupporting
confidence: 74%
“…15 The mechanism by which the 213Gly variant confers this protection comes from studies showing it alters the heparin binding site of the SOD3 protein reducing its affinity for the extracellular matrix and increasing its half life by reducing normal proteolytic cleavage. 17 It has been proposed that the secretion of uncleaved SOD3 (generated by the 213Gly variant) may result in a greater availability of SOD3 to provide an antioxidant or anti-inflammatory response. 17 22 However, it should be noted that a deleterious effect by reducing bound SOD3 to extracellular matrix has also been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal region of EC-SOD is important for the formation of tetramers (8)(9)(10), and the C-terminal region (Val-194-Ala-222) encompasses a heparinbinding region, which is responsible for the immobilization of EC-SOD in the extracellular matrix (11,12). The heparinbinding region of EC-SOD can be removed by an intracellular proteolytic event before secretion (13,14). Consequently, EC-SOD tetramers with no (type A), intermediate (type B), or high (type C) affinity for the extracellular matrix are produced (11,12).…”
mentioning
confidence: 99%